The immunobiology of SARS-CoV-2 infection and vaccine responses: potential influences of cross-reactive memory responses and aging on efficacy and off-target effects - Collins, Craig P.; Longo, Dan L.; Murphy, William J. (Frontiers in Immunology, 2024)
Immune responses to both SARS-CoV-2 infection and its associated vaccines have been highly variable within the general population. The increasing evidence of long-lasting symptoms after resolution of infection, called post-acute sequelae of COVID-19 (PASC) or “Long COVID,” suggests that immune-mediated mechanisms are at play. Closely related endemic common human coronaviruses (hCoV) can induce pre-existing and potentially cross-reactive immunity, which can then affect primary SARS-CoV-2 infection, as well as vaccination responses. The influence of pre-existing immunity from these hCoVs, as well as responses generated from original CoV2 strains or vaccines on the development of new high-affinity responses to CoV2 antigenic viral variants, needs to be better understood given the need for continuous vaccine adaptation and application in the population. Due in part to thymic involution, normal aging is associated with reduced naïve T cell compartments and impaired primary antigen responsiveness, resulting in a reliance on the pre-existing cross-reactive memory cell pool which may be of lower affinity, restricted in diversity, or of shorter duration. These effects can also be mediated by the presence of down-regulatory anti-idiotype responses which also increase in aging. Given the tremendous heterogeneity of clinical data, utilization of preclinical models offers the greatest ability to assess immune responses under a controlled setting. These models should now involve prior antigen/viral exposure combined with incorporation of modifying factors such as age on immune responses and effects. This will also allow for mechanistic dissection and understanding of the different immune pathways involved in both SARS-CoV-2 pathogen and potential vaccine responses over time and how pre-existing memory responses, including potential anti-idiotype responses, can affect efficacy as well as potential off-target effects in different tissues as well as modeling PASC.